Stating Appointment Costs in SMS Reminders Reduces Missed Hospital Appointments: Findings from Two Randomised Controlled Trials - Hallsworth, Michael; Berry, Dan; Sanders, Michael; Sallis, Anna; King, Dominic; Vlaev, Ivo; Darzi, Ara (PLOS ONE, 2015)
Background Missed hospital appointments are a major cause of inefficiency worldwide. Healthcare providers are increasingly using Short Message Service reminders to reduce ‘Did Not Attend’ (DNA) rates. Systematic reviews show that sending such reminders is effective, but there is no evidence on whether their impact is affected by their content. Accordingly, we undertook two randomised controlled trials that tested the impact of rephrasing appointment reminders on DNA rates in the United Kingdom. Trial Methods Participants were outpatients with a valid mobile telephone number and an outpatient appointment between November 2013 and January 2014 (Trial One, 10,111 participants) or March and May 2014 (Trial Two, 9,848 participants). Appointments were randomly allocated to one of four reminder messages, which were issued five days in advance. Message assignment was then compared against appointment outcomes (appointment attendance, DNA, cancellation by patient). Results In Trial One, a message including the cost of a missed appointment to the health system produced a DNA rate of 8.4%, compared to 11.1% for the existing message (OR 0.74, 95% CI 0.61–0.89, P<0.01). Trial Two replicated this effect (DNA rate 8.2%), but also found that expressing the same concept in general terms was significantly less effective (DNA rate 9.9%, OR 1.22, 95% CI 1.00–1.48, P<0.05). Moving from the existing reminder to the more effective costs message would result in 5,800 fewer missed appointments per year in the National Health Service Trust in question, at no additional cost. The study’s main limitations are that it took place in a single location in England, and that it required accurate phone records, which were only obtained for 20% of eligible patients. We conclude that missed appointments can be reduced, for no additional cost, by introducing persuasive messages to appointment reminders. Future studies could examine the impact of varying reminder messages in other health systems. Trial Registration Controlled-Trials.com 49432571